2022
DOI: 10.3390/v14030649
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Reveal Several Novel Viruses from Canegrubs (Coleoptera: Scarabaeidae) in Central Queensland, Australia

Abstract: Canegrubs (Coleoptera: Scarabaeidae) are major pests of sugarcane crops in Australia, but despite long-term and intensive research, no commercially viable biological control agents have been identified. We used the RNA-Seq approach to explore the viriomes of three different species of canegrubs from central Queensland, Australia to identify potential candidates for biological control. We identified six novel RNA viruses, characterized their genomes, and inferred their evolutionary relationships with other clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Two conserved domains, the Viral_helicase1, and the ps-ssRNAv_RdRp-like, were identified in the polyprotein at aa positions 617-848 and 1,673-1,857, respectively. Similar conserved domains were found in those non-structural polyproteins encoded by related beny-like viruses [38,39,41,42] ChMBLV structural protein showed the highest BlastP similarity with that one encoded by DuV2, with 29.75% identity (Table 1). This protein encoded by the ChMBLV ORF2 is likely a coat protein, since the TMV_coat super family conserved domain was identified at aa position 108-180.…”
Section: Beny-like Virusessupporting
confidence: 56%
See 1 more Smart Citation
“…Two conserved domains, the Viral_helicase1, and the ps-ssRNAv_RdRp-like, were identified in the polyprotein at aa positions 617-848 and 1,673-1,857, respectively. Similar conserved domains were found in those non-structural polyproteins encoded by related beny-like viruses [38,39,41,42] ChMBLV structural protein showed the highest BlastP similarity with that one encoded by DuV2, with 29.75% identity (Table 1). This protein encoded by the ChMBLV ORF2 is likely a coat protein, since the TMV_coat super family conserved domain was identified at aa position 108-180.…”
Section: Beny-like Virusessupporting
confidence: 56%
“…Benyviruses are plant-infecting viruses with a multipartite genome [37]. Nevertheless, metagenomic studies as well as the metatrancriptomic analysis of publicly data deposited in NCBI resulted in the discovery of many benyviruses related sequences, that resemble to newly unassigned Benyviridae members, that likely infect a wide range of non-plant hosts, such as insects and fungi [38][39][40][41]. Moreover, the insect-associated beny-like viruses genomes are monopartite which is contrasting to the multipartite genomes displayed by the plant-associated counterparts.…”
Section: Beny-like Virusesmentioning
confidence: 99%
“…Additionally, various studies have reported RNA viruses associated with agricultural insects of the order Coleoptera. These include the discovery of bee-associated viruses in Aethina tumida [138] , several novel RNA viruses in Dermolepida albohirtum [139] , an orthomyxovirus in Ips typographus , a chuvirus and a phenuivirus in Larinus minutus [5] , and an iflavirus in Aulacophora lewisii [140] .…”
Section: Rna Viruses In Agricultural Insects Of Different Ordersmentioning
confidence: 99%